Analisis Kesalahan Berbahasa pada Cerpen yang Berjudul Badai yang Reda dan Hutan Merah Karya Fauzia sebagai Kelayakan Bahan Ajar Membaca Intensif Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Semarang - Tri Maria Hastuti; Amanda Ayu Ningrum; Tyas Rahma Viani; Seruni Yunita Chairunnisa; Muhamad Syafiq Asyam; Asep Purwo Yudi Utomo; Rujiani Rujiani (Pusat Riset dan Inovasi Nasional, 2024)
Language use in everyday life is often incorrect, particularly in informal conversations. The correct and proper use of language also impacts an individual's reading process. Quality writing is characterized by the use of good and correct language conventions. However, many still encounter language errors in texts. Analyzing syntactic errors in short stories is necessary to identify and explain them. The aim of this study was to analyze language errors in the short stories